Being there but where? Sense of presence theory for virtual reality applications - Stefano Triberti; Caterina Sapone; Giuseppe Riva (Humanities & Social Sciences Communications)
The sense of presence—the psychological experience of “being there”—has emerged as a critical phenomenon in Virtual Reality (VR) research. While traditional approaches have predominantly focused on technological features as primary drivers of presence, this paper argues that such a view is fundamentally incomplete. We contend that presence is primarily a psychological phenomenon shaped by three critical dimensions that extend beyond mere technological sophistication: (1) the impact of content and narrative structure in virtual environments, (2) the influence of users’ individual characteristics and socio-cultural contexts, and (3) the relationship between presence and users’ intentional structures. Through a synthesis of current evidence, we demonstrate that these psychological and social factors often outweigh technical considerations in determining the quality of presence experiences. As immersive technologies become increasingly prevalent in shared environments and sensitive contexts such as education and healthcare, this more sophisticated understanding of presence becomes crucial for designing effective virtual experiences. We argue that future VR development should shift from a predominantly technology-centered approach to one that carefully considers these psychological and social dimensions to achieve intended outcomes while accounting for individual and cultural variability.